Morphology Design Paradigms for Supercapacitors - Inamuddin, 1980-; Boddula, Rajender; Ahmer, Mohammad Faraz; Asiri, Abdullah M. (Milton : CRC Press LLC, 2020)
Nanostructured electrode materials have exhibited unrivaled electrochemical properties in creating elite supercapacitors. Morphology Design Paradigm for Supercapacitors presents the latest advances in the improvement of supercapacitors, a result of the incorporation of nanomaterials into the design -from zero-dimensional to three-dimensional, and microporous to mesoporous.The bookincludes a comprehensive description of capacitive practices at the levels of sub-atomic and nanoscales. These have the ability to enhance device performance for an extensive assortment of potential applications, including consumer electronics, wearable gadgets, hybrid electric vehicles, stationary and industrial frameworks. Key Features: Provides readers with a clear understanding of the implementation of these materials as electrodes in electrochemical supercapacitors. Covers recent material designs and an extensive scope of electrode materials such as 0D to 3D. Explores recent nanostructured-system material designs that have been created and tested in supercapacitor configurations. Considers microporous to mesoporous supercapacitor electrode materials. Features the impact of nanostructures on the properties of supercapacitors, including specific capacitance, cycle stability, and rate capability.
Chapter 8: Chemical Synthesis of Hybrid Nanoparticles Based on Metal-Metal Oxide Systems -- Chapter 9: Inorganic One-Dimensional Nanomaterials for Supercapacitor Electrode Applications -- Chapter 10: One-Dimensional Carbon Nanostructures for Supercapacitors -- Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Supercapacitors; SCIENCE / Chemistry / General; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY / Material Science